MODEL PEMBELAJARAN BAHASA JEPANG OLEH GURU BAHASA JEPANG SMA SE-KOTA PEKANBARU - Amorita, Nessie Illona; Sinaga, Mangatur; Rahayu, Nana (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: The purpose of this study is to determine the Japanese languagelearning model of high school Japanese language teachers throughout Pekanbaru. The Respondents of this study were 6 Japanese language teachers from four different high schools, namely SMA Negeri 8 Pekanbaru, SMA Negeri 9 Pekanbaru, SMA Al-Azhar Syifa Budi Pekanbaru, and SMA Cendana Pekanbaru. The sampling technique of this study was Saturated Sampling. This technique is the determination of the sample whenall members of the population are used as samples. The Data collection techniques was by distributing the questionnaires, conducting the interviews, observation and equipped with documentation. The research method used was quantitative descriptive, Which was Explaining a situation that occurs based on the data (numbers) that have been obtained. The results of this study were, the Japanese language learning model of high school Japanese language teachers in Pekanbaru was in the good category/ always (> 50%) applying the learning model, with an average percentage acquisition of 70.77% and was in accordance with the model 2013 curriculum learning which was centered onstudents.Key Words: 2013 Curriculum, Learning Model, Scientific Approach